Globalisation and consumer rights: Emerging dimensions - Globalisation and Consumer Rights (Seminar) (2011 : Fakir Mohan University); Dash, G. (Geetanjali), 1961- (New Delhi: Abhijeet Publications, 2013)
Papers presented at the national seminar on "Globalisation and Consumer Rights", held at Fakir Mohan University during 25-26 November 2011.
Section A. Globalisation and consumer rights -- section B. Ethics and consumer rights -- section C. Service section and consumer protection -- section D. Globalisation and rural consumer.
Includes bibliographical references.
Keywords: Consumer protection -- Law and legislation -- India -- Congresses; Consumption (Economics) -- Moral and ethical aspects -- India -- Congresses; Service industries -- India -- Congresses; Financial services industry -- Customer services -- India -- Congresses; Globalization -- Economic aspects -- India -- Congresses; Services (Industries) -- Inde; Services financiers -- z; Mondialisation -- Inde; Consumer protection -- Law and legislation; Consumption (Economics) -- Moral and ethical aspects; Financial services industry -- Customer services; Globalization -- Economic aspects; Service industries; India; Conference papers and proceedings